The MODIFIKASI MODEL PEMBELAJARAN HEURISTIC VEE MENINGKATKAN PEMAHAMAN KONSEP DAN KREATIVITAS MATEMATIS MAHASISWA FKIP UHN MEDAN - ruth mayasari simanjuntak (Fakultas Keguruan dan Ilmu Pendidikan, Universitas HKBP Nom- mensen, 2020)
The objective of the research id to modify the heuristic vee learning model to improve student’s understanding of mathematical concepts and to improve student’s mathematical creativity abilities as well as to see the interaction between heuristic vee learning models with their level of mathematical ability towards increasing student’s understanding of mathematical concepts and mathematical creativity. This research was implemented at Nommensen HKBP University and experimental study with a pre-test post-test control group design research design. The population is all fourth semester students by taking a sample of two classes through random sampling techniques. The data is obtained through semester scores for KAM, tests of mathematical understanding abilities, tests of mathematical creativity abilities. The data were analysed by two-way ANAVA test. Before using the two-way ANAVA test, homogeneity tests were used in the study and normality in this study was 5% significant. The problem solving process created by students is expected to meet the criteria of understanding and mathematical creativity in the learning group Heuristic Vee Learning Model. The research findings recommend a modification of the Heuristic Vee learning model as one of the learning approaches used on campus